ASPECTS OF THE DEVELOPMENT OF THE PROGRAM OF PALLIATIVE ASSISTANCE FOR CHILDREN OF THE KHARKIV REGION THROUTH THE CHALLENGES OF THE MILITARY CONFLICT - О. Ріга; Д. Марстон; М. Хаустов; В. Мясоєдов; А. Пеньков; Р. Марабян (Bukovynian State Medical University, 2023)
In the context of armed confl ict, palliative care, pain management, and care for the dying and bereaved require increased and urgent attention. The devastating humanitarian crisis in Ukraine makes these issues even more critical. In 2021, a project working group was created in the Kharkiv region to prepare the program for the implementation of palliative care for children in the Kharkiv region. The main reasons for the imperfect development of pediatric palliative care in Kharkiv region were some points such as: lack of a systematic vision of the organization of pediatric palliative care services; acute shortage of qualifi ed medical personnel, lack of educational programs and opportunities to study best practices in this fi eld; lack of relations between primary and secondary (tertiary) links of medical care and coordination; lack of formulations of children's drugs for pain relief and fear of prescribing opioid analgesics; an imperfect system of informing medical workers about the rights of children as patients; lack of interdisciplinary cooperation in the fi eld of providing pediatric palliative care (education, social services, clergy, lawyers, economists); lack of joint programs between health, social and education departments in the fi eld of pediatric palliative care; lack of a state policy in the fi eld of pediatric palliative care; lack of a system for fi nancing pediatric palliative care measures and monitoring their eff ectiveness. Before the war, the approximate number of children in need of palliative care in the Kharkiv region was 9,000 - 10,000, plus an estimated 21,000 - 25,000 family members. As of January 1, 2022, there were 426,000 children under the supervision of health care institutions in the region. 216,900 children lived in the city of Kharkiv, 209,700 in the rural areas. In the pre-war period there were 9,372 children with disabilities in the Kharkiv region. The structure of the causes of disability was as follows: congenital malformations - 25.5% (2389 children), diseases of the endocrine system - 16.4% (1537 children), diseases of the nervous system - 16.0% (1497 children), mental and behavioral disorders 13.8% (1295 children), ear diseases - 9.2% (862 children). The authors' vision is: to start policy development and creation of an eff ective system of pediatric palliative care in accordance with the needs and international standards; creation of an eff ective system of training of medical and social workers in pediatric palliative care protocols and standards; development of coordinated pediatric palliative care at the place of residence/stay of the child; mobile teams; hospital beds and hospital teams; wide public awareness and involvement of public organizations in the provision of pediatric palliative care; attraction of budgetary and extra-budgetary funds for fi nancing pediatric palliative care. Authors also speculate that other important steps need to be implemented to regional program of pediatric palliative care and integrated with international recommendations and organizations.